THE EFFECT OF AEROBIC EXERCISE ON BLOOD GLUCOSE LEVELS AMONG PATIENTS WITH TYPE 2 DIABETES MELLITUS: A QUASI-EXPERIMENTAL STUDY - Puspasari, Susy; Sarita, Friska Rahma (Medical-Surgical Journal of Nursing Research, 2025)
Type 2 diabetes mellitus (T2DM) is characterized by persistent hyperglycemia, leading to long-term complications if not well managed. Physical activity, particularly aerobic exercise, has been shown to improve glycemic control through enhanced insulin sensitivity and glucose uptake. This study aimed to evaluate the effect of a structured aerobic exercise program on blood glucose levels among patients with T2DM. A quasi-experimental, one-group pretest-posttest design was used. Thirty-eight patients with T2DM were recruited through purposive sampling at a primary healthcare center. The intervention consisted of a supervised aerobic exercise program conducted three times per week for four weeks. Blood glucose levels were measured using a calibrated glucometer before and after the intervention. Data were analyzed using paired t-tests, with significance set at p < 0.05. A total of 34 participants completed the intervention. The mean pre-intervention blood glucose level was 176.76 ± 25.07 mg/dL, while the post-intervention level was 114.79 ± 13.76 mg/dL. The decrease was statistically significant (mean difference = 61.97 mg/dL, t = 11.86, p < 0.001). Aerobic exercise significantly reduced blood glucose levels in patients with T2DM. These findings support the integration of structured exercise into diabetes management protocols, particularly in community settings.